The Law of Tax-Exempt Organizations, 12th Edition - Hopkins, Bruce (Wiley, 2019)
Tax-exempt law explained, for lawyers and nonlawyers alike The Law of Tax-Exempt Organizations has, for decades, been the definitive single-volume source of legal information for nonprofit lawyers and managers alike. Author Bruce R. Hopkins is widely recognized as the leading authority on the subject; in this thoroughly revised Twelfth Edition, he provides all the updates you need to stay current on the latest changes to tax code, regulatory, and case law developments. Annual supplements available with the book will ensure that you don't miss any important updates. Making solid decisions about the future of any tax-exempt organization requires a firm and up-to-date understanding of the relevant tax and other law. This reference provides guidance on the latest developments in eligibility for tax exemption, the private inurement and private benefit doctrines, nonprofit governance, lobbying, political campaign activity, public charities, private foundations, donor-advised funds, unrelated business activities, reporting, disclosure requirements, and more. Understand the tax code, regulations, and case law pertaining to all categories of tax-exempt organizations Access the nonprofit law standard reference guide, written by the leading legal expert on tax-exempt organizations Prepare yourself to make well-founded strategic decisions about the current and future actions of your organization Review annual supplements that provide plain-English information on changes for each tax year Written in a practical format that's accessible to lawyers and non-lawyers alike, The Law of Tax-Exempt Organizations, Twelfth Edition, is a trustworthy resource for anyone involved in advising or managing charitable organizations, social welfare entities, associations, clubs, or any other type of tax-exempt entity.